AN EFFORTS TO IMPROVE DIGITAL LITERACY TEACHERS THROUGH THE CREATION OF ELECTRONIC BOOK - KUSMURIYANTO; KARDIYEM; DWI PUJI ASTUTI; RAHAYU LESTARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The purpose of this devotion program is for teachers at SMK YPPM Boja to have the knowledge and ability to design more creative, innovative, and exciting learning media. Besides, it can realise the reduction of paperless use in supporting environmental conservation. It is high time the learning media switched from paper book to digital book, considering paper-based books are impractical and heavy to carry, easily damaged and lost. E-book can be the right solution for practical, secure, and accessible learning media. E-book is also a great way to reduce paper use and reduce the flight of trees as paper raw materials, making it more environmentally friendly. This method of community service takes the form of lectures, discussions, and practices. The materials that are delivered include the definition of learning media, types of learning media, the introduction of Electronic Book as a digital learning medium, the excellence of e-book, the techniques and stages of the preparation of e-book, and the implementation of e-book as a learning medium. The result of this community service is the increasing understanding of SMK YPPM Boja teachers in the creation of exciting learning media as well as improving the professional competencies of teachers.